Polemik Batas Minimum Usia Anak yang Dapat Dipidana pada Kasus Kekerasan Seksual Berujung Hilangnya Nyawa - Eva Albatun Nabilah; Vinny Alvionita; Andi Sri Hastuti Handayani Usman; Eka Darmayanti Putri Siregar; Olivia Pamilangan Andilolo (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to see the determination of the minimum limit of criminal liability for children in conflict with the law after the emergence of the rape and murder case of a junior high school student in Palembang in August 2024 where the three perpetrators who were under 14 (fourteen) years old were not sentenced but only in the form of actions. This research is a normative legal research that uses a statutory approach and a case approach. The results of this study indicate that when referring to the provisions of international law on children, namely the CRC and its General Comments and the Beijing Rules, the determination of the minimum age of criminal liability for children and the minimum age of children can be punished in national law, namely the SPPA, is appropriate so that there is no need for changes. There are three solutions to dealing with cases of children committing sexual violence in the future that the government can do, namely: Strengthening parental responsibility in supervising digital literacy and strengthening family socio-economics, psychological approaches to children and the importance of sex education